The Impact of Sales Promotion and Ewom on Consumer’s Actual Purchase Online in Kuala Lumpur, Malaysia: a Study on Generation-Y - Khadija Mansoor Ali; Aeshah Mohd Ali; Nurfaradilla Haron; Nor Aziyatul Izni (International Journal of Educational Excellence and Innovation, 2024)
The study aims to see the influence of sales promotion (SP) and Electronic Word-of-Mouth (eWOM) on customers’ actual purchases online (CAPO) in Kuala Lumpur, Malaysia. As Malaysia is still facing several challenges regarding economic structure and development disparities, therefore, this study will help organizations in Malaysia to better understand the importance of social networking sites (SNS) and its impact on CAPO. The independent variables are SP and eWOM and the dependent variable is CAPO. Technology adoption model (TAM) theory has been applied and the sampling technique used is probability stratified sampling. The sample size of the study is 200 respondents and the students from the private university have been selected who possess undergraduate and postgraduate programs and experienced online purchasing. The results found that there is a significant correlation between SP, EWOM, and CAPO. Therefore, the results concluded that young individuals are highly influenced towards online purchasing, due to SNS.